Increasing ABB FlexPicker Robot’s Degree Of Freedom (DOF) Using Flexible End Effector - Mohd Hisham, Nordin; Kalaiselvan , Selvaraju; M., Fathullah (EDP Sciences, 2016)
The commissioning of a high speed parallel robot such as the ABB Flexpicker Robot into the industrial environment provides greater flexibility in picking, packaging or palletizing tasks. However, current configuration of this robot only allows up to four-degree-of-freedom (DOF) which restricted its function to perform simple or complex automated assembly task. Therefore, the possibility of increasing one additional degree-of-freedom for the parallel robot was investigated. By attaching a flexible vacuum hose to the robot’s end effector, it can be controlled by using a servomotor that can manipulate its angle of suction up to 90 degrees. With this new configuration, one DOF has been introduced for this robot. Several tests had been conducted to evaluate the flexibility and performance of the end effector which includes varying loads and angles. From the analysis, it is found that the end-effector can lift weights up to 1kg due to sufficient vacuum pressure; however, it could perform bending up to 90 degrees for maximum load of 600 grams only.